A Binary Medium Model for Frozen Silty Sand Simplified by Breakage Parameter. (16th August 2022) - Zhang, Shuming; Jiang, Guanlu; Cai, Junfeng; Ye, Xiongwei; Luo, Bin; Yuan, Shengyang
Abstract : In order to investigate the strength-deformation characteristics of frozen silty sand, the triaxial compressive strength tests of saturated frozen silty sand under different fine particle contents were carried out, and the binary medium theory was introduced to interpret the stress-strain relationship. Due to the characteristics of the existing binary medium model with many parameters and complicated determination method, a simplified binary medium model based on breakage parameter is proposed. The derived model was verified by the triaxial tests of frozen silty sand. The results show that the stress-strain relationship can be divided into three stages with the increase of axial strain, namely, linear elastic deformation stage, plastic deformation stage, and strain softening stage. All three stages can be well explained by the transformation theory of bonded element and frictional element with the binary medium model. In the linear elastic deformation stage, the external stress is mainly borne by the bonded element. In the plastic deformation stage, the stress sharing ratio of the bonded element decreases and that of the frictional element increases. In the strain softening stage, the stress sharing ratio of the bonded element decreases rapidly, while that of the frictional element increases rapidly. Under the same confining pressure, both deviator stress and the maximum values of bulk expansion decrease, while the shear strength decreases linearly with the increase of fine particle content. By comparing the measured deviator stress in triaxial test with the calculated values of binary medium constitutive model simplified by breakage parameter, the proposed model can better simulate the stress-strain relationship of frozen silty sand. The results of the study can provide some theoretical reference for the constitutive model of seasonal frozen soil.